Seizures in Dogs and Cats. - Sanders, Sean (Wiley, 2015)
Seizures in Dogs and Cats offers a practical, complete resource for the veterinary management of seizures in dog and cat patients. The book is carefully designed for ease of use in the clinical setting, presenting clinically oriented information on the etiology, diagnosis, and management of seizures. Each chapter begins with key points, then presents greater detail, making the book equally useful for fast access during the exam and for further reference. The book begins with chapters on the history, biology, and classification of seizures, then covers diagnosis, medical and surgical treatm.